The Analysis of Economic and Traffic Feasibility of Flyover Ganefo Mranggen Demak Construction - Adiguna , Giris Nuryanto; Widyastuti, Hera; Anak Agung, Gde Kartika (Jurnal Transportasi: Sistem, Material, dan Infrastruktur, 2023)
Traffic jam is a common problem for the Demak Society. One of the causes of the traffic jam occured in Demak Regency is the road section that cannot accommodate the vehicle volume. Every day, the vehicle volume keeps increasing, but it is not followed by road facility improvement. One of the areas that is prone to traffic congestion in Demak Regency is the crossroad between the road and railroad of Ganefo Mranggen, which located on Karangawen road. It connects Semarang Regency and Demak Regency. In general, traffic jam on this road occurs during rush hours, such as when the workers start going to work and back home from their workplace. Considering the phenomenon, it is necessary for Demak government to build an infrastructure that can solve the traffic congestion problem. Flyover construction can be a way to manage traffic congestion in the congestion center. By constructing this flyover on Karangawen road, it will save travel time for road users when passing the flyover compared to the existing road. Therefore, a Study of the Economic and Traffic Feasibility of Flyover Ganefo Mranggen Demak Construction was carried out. This feasibility study compared the user cost with the vehicle volume, and the degree of saturation (DS) before and after the flyover was constructed. In addition, the study of economic feasibility was reviewed from BCR (Benefit Cost Ratio) and NPV (Nett Profit Value) from this Flyover Ganefo Mranggen construction. The method used to analyze the Vehicle Operating Cost (VOC) was the Jasa Marga method. The data was collected using the survey traffic counting method. The result of this study obtained the feasibility calculation of Flyover Ganefo Mranggen construction was Benefit Cost Ratio (BCR) =1,12 Net Present Value (NPV)=IDR 38.330.261.991.14. According to the result, it can be concluded that the Flyover Ganefo Mranggen Demak construction is stated feasible economically.